1999
DOI: 10.1002/j.2161-0045.1999.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Ethnic and Nonethnic Variables on the Career Decision‐Making Self‐Efficacy of College Students

Abstract: This study examined differences in career decision-making self-efficacy, trait anxiety, and ethnic identity for 687 undergraduates (589 Whites, 98 racial and ethnic minorities). Significant differences by race and major (declared, undeclared) indicated that White students had higher career decision-making selfefficacy and lower trait anxiety, ethnic identity, and other-group orientation. Declared students had higher career decision-making self-efficacy and lower trait anxiety. Ethnic variables (ethnic identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
126
5
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(145 citation statements)
references
References 32 publications
12
126
5
2
Order By: Relevance
“…However, this study did not mirror Gloria and Hird's (1999) findings that White college students had greater career decision self-efficacy than college students of color. In this study, African American participants reported significantly greater confidence in their ability to make career decisions in comparison to Asian American participants after using FOCUS-2.…”
Section: Impact Of Gendercontrasting
confidence: 99%
“…However, this study did not mirror Gloria and Hird's (1999) findings that White college students had greater career decision self-efficacy than college students of color. In this study, African American participants reported significantly greater confidence in their ability to make career decisions in comparison to Asian American participants after using FOCUS-2.…”
Section: Impact Of Gendercontrasting
confidence: 99%
“…An additional study found that African American students reported significantly higher career decision-making self-efficacy than did students from other ethnic backgrounds, including Native American, Asian American, and Caucasian American students (Chaney, Hammond, Betz, & Multon, 2007). Although several studies have reported higher career decision-making self-efficacy scores among African American individuals (e.g., Betz & Luzzo, 1996;Chaney et al, 2007;Chung, 2002), Gloria and Hird (1999) found significant differences within a sample of diverse undergraduate students, with Caucasian Americans scoring significantly higher. In summary, previous research has made a strong case for the study of cultural mistrust in relation to these more commonly studied vocational variables, indicating possible relationships with self-efficacy and negative thinking.…”
Section: September 2011 • Volume 59mentioning
confidence: 90%
“…The Career Decision-Making Self-Efficacy Scale has already been used in a number of studies on career decision-making. It appears that scores for the Career Decision-Making Self-Efficacy Scale are related to the individual's career decision-making status (Gianakos, 1999;Robbins, 1985;Taylor & Popma, 1990), career identity (Robbins, 1985), career decision-making difficulties (Osipow & Gati, 1998), self-worth (Robbins, 1985), trait-anxiety (Gloria & Hird, 1999), exploratory behaviour (Blustein, Ellis & Devenis, 1989;Brown, Glastetter-Fender & Shelton, 2000), locus of control (Brown et al, 2000;Taylor & Popma, 1990) and willingness of women to consider non-traditional careers (Foss & Slaney, 1986). It would therefore appear that the Career DecisionMaking Self-Efficacy Scale relates to a variety of career-related constructs in a meaningful manner.…”
mentioning
confidence: 99%